Traumatic vulva hematoma in children: Mechanism and management - Moufidath Sounkere-Soro; Yapo Guy Serge Kouamé; Helen Thomas; Jean Baptiste Yaokreh; Samba Tembely; Thierry Odehouri-Koudou; Dibi Bertin Kouamé; Ossenou Ouattara (Elsevier, 2022)
Traumatic vulvar hematomas are rare in children. they are most often due to perineal blunt trauma in non obstetric population. Management was not establishing and conservative treatment alone is sufficient in most cases. The time to surgery and their indications must be precise to avoid complication. This is a report of a teenager who presented with a large right vulva hematoma after pubic blunt trauma. Surgical intervention was done faced to the failure of initial conservative treatment. The outcome was uneventfull.